2009
DOI: 10.1002/cctc.200900099
|View full text |Cite
|
Sign up to set email alerts
|

Probing Surface Properties and Reaction Intermediates During Heterogeneous Catalytic Oxidation of Acetaldehyde

Abstract: The influence of Cu on various metal oxide supports was investigated for the catalytic oxidation of acetaldehyde (ACA). The activity of the catalysts towards ACA conversion and the CO2 yield decrease in the order: Cu/CeO2>Cu/TiO2≈Cu/ZrO2> Cu/Al2O3>Cu/SiO2. Spontaneous adsorptive conversion of ACA to surface carboxylates, such as bridging and bidentate acetates, was detected over the basic supports CeO2, TiO2, and ZrO2. Detailed temperature‐programmed studies found the high activity of Cu/CeO2 to stem mainly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The presence of acetate species can be deduced by the 1456 and 1513 bands, due to -COOsymmetric and antisymmetric stretching, respectively. 52 Spectral characteristic features of acetaldehyde at 1691 cm À1 n(C]O) was also found in the used catalysts. Characteristic bands of the condensation product crotonaldehyde appeared at 1658 and 1634 cm À1 .…”
Section: Catalysts Characteristics Aer Reactionmentioning
confidence: 82%
“…The presence of acetate species can be deduced by the 1456 and 1513 bands, due to -COOsymmetric and antisymmetric stretching, respectively. 52 Spectral characteristic features of acetaldehyde at 1691 cm À1 n(C]O) was also found in the used catalysts. Characteristic bands of the condensation product crotonaldehyde appeared at 1658 and 1634 cm À1 .…”
Section: Catalysts Characteristics Aer Reactionmentioning
confidence: 82%
“…A higher basicity has been reported to correlate to a more ionic surface, which would be able to donate electron density from surface O to the α-carbon of acetaldehyde, therefore oxidizing the acetaldehyde and leading to acetate groups. 12 The cubes displayed bands associated with acetate groups (and the octahedra, to a lesser extent) in the TP-DRIFTS. However, the wires produce a large amount of acetone in the TPD, compared to the small amounts observed on the cubes and none on the octahedra.…”
Section: ■ Discussionmentioning
confidence: 97%
“…10 Previously, experiments have shown that CeO 2 is an active catalyst to promote the coupling of acetaldehyde, an oxygenate species, to form several products including crotonaldehyde, crotyl alcohol, butane, butadiene, and acetone. 11,12 Oxygenates have garnered much attention as fuel additives, as components obtained from the processing of biomass, and as an intermediate for value-added products. 13 However, the conversion of oxygenates upon catalysis is not well-understood.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This finding indicates that the photocatalytic active component may not be a semiconductor mechanism. For a semiconductor photocatalyst, photons with energy larger than the bandgap (the light with shorter wavelength) could cause reactions on it 1719. Given that AgI has a bandgap of 2.8 eV, the irradiation with λ >443 nm cannot initiate the photocatalysis reaction.…”
Section: Phase Composition and Specific Surface Area Of Ag2o@tnts Anmentioning
confidence: 99%